Sociocultural Theory and Its Implications for Islamic Education (PAI) Learning in Elementary Schools - Ayu Annur Fani; Ermis Suryana; Zulhijra Zulhijra (Journal of Educational Sciences, 2026)
Elementary school education plays a strategic role in shaping students’ cognitive, social, and emotional development; however, teacher-centered learning practices often fail to provide optimal opportunities for meaningful social interaction. This study aims to describe the socio-cultural theory of Lev S. Vygotsky and its implications for Islamic Religious Education (PAI) learning at the elementary level, specifically at SDN 16 Talang Kelapa, Banyuasin Regency. This research employs a descriptive qualitative approach using a case study method to investigate the phenomenon in depth. The findings indicate that the implementation of socio-cultural learning theory in PAI instruction at SDN 16 Talang Kelapa, based on the Merdeka Curriculum, demonstrates that social engagement and interaction among students enhance their understanding of religious concepts in a deeper and more contextual manner. Through collaboration, group discussions, and habitual reflective activities, students not only comprehend the material cognitively but also internalize religious values in their daily lives. Thus, socio-cultural theory is proven effective in fostering active, meaningful, and student-centered learning.